Adulterated dietary supplements threaten the health and sporting career of up‐and‐coming young athletes. Issue 3 (2nd November 2015) - Eichner, Amy; Tygart, Travis
Abstract : The authors provide the perspective of the United States Anti‐Doping Agency on the actions youth sport organizations should take to protect the health of developing young athletes.